Combined effects of cryogenic treatment and tempering on microstructural and tribological features of AISI H13 steel - Gecu, Ridvan (ELSEVIER SCIENCE SA, 2022)
AISI H13 hot work tool steels were subjected to shallow and deep cryogenic treatment. One set of the samples was single tempered, while the other set was double tempered. Cooling specimens to-196 degrees C increased martensite content and hardness. After tempering, martensite morphology changed, carbides of Cr7C3 and V2C precipitated, and some retained austenite transformed again. Hardness decrease remained limited due to carbide formation. Both cryogenic treatments and tempering processes improved the wear resistance, although the effect of double tempering seemed nebulous. Worn surface analysis revealed that delamination and abrasion pre-dominantly occurred during sliding based on microstructural alteration.
Keywords: Cryogenic treatment; Hot work tool steel; AISI H13; Tempering; Wear; WEAR-RESISTANCE; TOOL STEEL; PRECIPITATION BEHAVIOR; MECHANICAL-PROPERTIES; CARBIDES; COMPOSITE; Materials Science